Analysis Of Non Poor Households Have Received Conditional Cash Transfer - Sembiring, Roy Karten (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
This study aims to analyze HDI achievements, HDI disparities, and regional characteristics based on HDI achievements in South Sumatra Province. This research is a quantitative descriptive study using secondary data from the official website www.bps.go.id. This study uses an Interval Scale, Williamson Index, and Klassen Typology. The results show that the decline in the purchasing power of the people of South Sumatra in 2020 has contributed to the contraction of HDI growth in South Sumatra Province. The disparity in human development in South Sumatra Province in the 2016-2020 period shows a declining trend. Klassen's Typology analysis result shows: 1) fast growing areas are Ogan Komering Ulu and Muara Enim Regency; 2) developed but distressed areas are Palembang City, Prabumulih City, Lubuk Linggau City, andOKU Timur Regency; 3) developing areas are Musi Rawas Regency, Banyuasin Regency, OKU Selatan Regency, Ogan Ilir Regency, Penukal Abab Lematang Ilir Regency, Musi Rawas Utara Regency, and Pagar Alam City; and 4) relatively underdeveloped areas are Ogan Komering Ilir Regency, Lahat Regency, Musi Banyuasin Regency, and Empat Lawang Regency.